WTO Dispute Settlement Understanding and Development. - Martin, Mervyn (Nijhoff international trade law series., 2013)
This book examines the effectiveness of the World Trade Organisation (WTO) Dispute Settlement Understanding (DSU) in pursuing the developmental objectives of the WTO is a whole.